Fuel cell electrode, catalyst-coated separator, fuel cell, and method for preparing fuel cell electrode and catalyst-coated separator

By adding an appropriate amount of halogen ions to the fuel cell electrode and forming a combination of metal-containing catalyst and proton-conducting ionomers, the problem of catalyst degradation is solved, the long-term stability and performance of the fuel cell are improved, and efficient stability improvement is achieved.

CN119137771APending Publication Date: 2024-12-13GREENERITY GMBH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380037079.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-21
Filing Date
2023-03-15
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing fuel cell electrodes are susceptible to toxicity by halogen ions during use, resulting in catalyst degradation and performance losses, affecting long-term stability.

Method used

The concentration is adjusted by actively adding 50 to 1000 ppm of halogen ions, especially chloride ions, to the fuel cell electrode, to form a combination of metal-containing catalyst and proton-conducting ionomers to prevent catalyst degradation and to a separator coated with catalyst Halogen ions are evenly distributed.

Benefits of technology

The long-term stability of fuel cell electrodes and separators is significantly improved, prevents catalyst degradation, maintains good performance, and achieves stability improvement without increasing technical and time costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119137771A_ABST
    Figure CN119137771A_ABST
Patent Text Reader

Abstract

The invention relates to a fuel cell electrode (2, 3) comprising a metal-containing catalyst (5, 7) and a proton-conducting ionomer (6, 8) wherein the fuel cell electrode (2, 3) has a halide ion concentration of 50 to 1000 ppm relative to the total mass of the fuel cell electrode (2, 3).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a fuel cell electrode, a catalyst-coated membrane, a fuel cell, and a method for preparing the fuel cell electrode and the catalyst-coated membrane.

[0002] It is known from the prior art that halogen ions (and in particular chloride ions) may reduce the functionality or long-term stability of the membrane electrode assembly of the fuel cell. Here, the halogen ions can be introduced into the membrane electrode assembly via various routes, for example, by using a halogen ion-containing precursor compound for a catalyst (e.g., H2Pt(Cl)6, etc.) to be used in the electrode of the membrane electrode assembly.

[0003] Under actual operating conditions, the MEA undergoes potential cycles, i.e. alternating phases of higher and lower potential. Here, the catalyst in the fuel cell electrode, especially the platinum usually on the cathode side of the MEA, undergoes repeated reduction and oxidation. This in turn leads to repeated dissolution and precipitation of the platinum, whereby individual catalyst particles may agglomerate, which is known as "Ostwald ripening", whereby the catalyst surface is reduced during operation and thus loses performance.

[0004] Guilminot et al. (J. Electrochem. Soc. 2007, 154 (1), B96-B105) reported that platinum-based and carbon-supported (Pt / C) catalysts were poisoned by halogen ions and the catalytic activity was reduced as a result. It should also be noted that adsorbed halogen ions facilitate the (electro)chemical dissolution of Pt or PtO.

[0005] For example, in DE102018002337 A1, halogenated intermediates when preparing perfluoropolymers such as those used in fuel cell membranes and as ionomers in fuel cell electrodes are described as the cause of halogen ion pollution. In DE102018002337 A1 and in Electrochimica Acta 52 (2007) cited therein: 7444-7552, platinum dissolution enhanced by chloride ions or bromide ions is mentioned, wherein a very small proportion of about 1ppm has been described as having a negative effect. A chloride ion concentration of 4ppm should have resulted in a voltage loss of 50mV. In addition, due to chloride ions, more H2O2 may be formed, which causes chemical degradation and therefore leads to weakening or pore formation in the diaphragm. DE102018002337 A1 therefore proposes a method for improving the long-term stability of MEA, wherein the amount of halogen ions is reduced by adding silver carbonate, forming silver halide and then irradiating and thereby decomposing silver chloride while releasing halogen ions.

[0006] Starting from the prior art cited above, the object of the present invention is to provide fuel cell electrodes, catalyst-coated membranes and also fuel cells with improved long-term stability, which do not suffer performance losses during the intended use. In addition, the object of the present invention is to propose methods for producing long-term stable fuel cell electrodes and long-term stable catalyst-coated membranes and also fuel cells, which methods can be implemented simply and cost-effectively and improve the long-term stability of the fuel cell electrodes and also the catalyst-coated membranes and the fuel cells without causing performance losses.

[0007] To this end, the fuel cell electrode of the present invention comprises a metal-containing catalyst and a proton-conducting ionomer. The fuel cell electrode can be formed as a cathode or an anode. Accordingly, the fuel cell electrode also comprises a corresponding metal-containing catalyst, i.e., in the case of a cathode, a metal-containing catalyst for reducing oxygen (in the catalyst-coated diaphragm of the present invention, such catalyst corresponds to the first metal-containing catalyst) and in the case of an anode, a metal-containing catalyst for oxidizing hydrogen (in the catalyst-coated diaphragm of the present invention, such catalyst corresponds to the second metal-containing catalyst). The proton-conducting ionomers of the anode and cathode can be the same or different.

[0008] The fuel cell electrode is characterized by a halogen ion concentration of 50 to 1000 ppm relative to the total mass of the fuel cell electrode. This means that the fuel cell electrode actively adds halogen ions, for example in the form of a solution containing halogen ions. The halogen ion concentration of 50 to 1000 ppm also takes into account any halogen ion amount already contained in the individual components of the fuel cell electrode. These can be, for example, halogen ions introduced by precursors containing metal catalysts or by ionomers. However, the amount of halogen ion concentration already contained in the individual components of the fuel cell electrode is small enough to be negligible and is particularly less than 20 ppm and particularly less than 10 ppm. That is, in order to achieve a halogen ion concentration of 50 to 1000 ppm, the fuel cell electrode actively adds at least one halogen ion. According to the present invention, the halogen ion concentration in the fuel cell electrode relates to the halogen ion concentration before the fuel cell electrode is used as intended.

[0009] The halogen ion concentration can be adjusted by adding a halogen ion or by adding a combination of two or more halogen ions. Halogen ions are not specifically limited here and are introduced into the fuel cell electrode in particular as dissolved salts. Halogen ions in fuel cell electrodes are determined by means of ion chromatography. Halogen ions can be distinguished by retention time via ion chromatography (retention time: for example, F: 6.9 minutes, Cl: 10.4 minutes, Br: 15.9 minutes). Here, a mixture of 1.9L of an aqueous solution of sodium carbonate with a concentration of 3.2mmol / L and sodium bicarbonate with a concentration of 1.0mmol / L and 0.1L of acetonitrile is used, resulting in a total of 2.0L of eluent. The measurement is performed with Metrohm 690IC (Germany, Deutsche METROHM GmbH & Co. KG). Metrosep A Supp7-250 / 4.0mm (Germany, Deutsche METROHM GmbH & Co. KG) is used as a column. The column temperature was set at 40 °C and the flow rate was 0.7 mL / min. -1 . In ion chromatography, free ions can be measured depending on the sample preparation method, that is to say fluorine covalently bonded to, for example, polymers is not detected. For this purpose, the halogen ions are extracted by water. If the halogen ion concentration is determined in one of the components of the fuel cell electrode, the sample can also be ashed and then measured. In order to determine the chloride ions, the sample preparation can be carried out by so-called oxygen pressure digestion. In this method, the sample material is incinerated in a closed system under pressure and with the addition of oxygen, and thus the covalently bonded analytes in the material are also released and measured by means of ion chromatography. Since the chloride ions are usually not contained in any component in a bonded state, the chloride ion concentration of the free chloride ions also corresponds to the chloride ion concentration in the entire fuel cell electrode.

[0010] Since the fuel cell electrode is used in particular together with a second fuel cell electrode and a membrane arranged between the two fuel cell electrodes when used as intended in a fuel cell, it is preferred that: only the fuel cell electrode of the present invention includes a halogen ion additive so that the halogen ion concentration of this fuel cell electrode is in the range of 150 to 6000 ppm; and no additional halogen ions are added to the second fuel cell electrode and the membrane.

[0011] Surprisingly, it has been found that the long-term stability of the fuel cell electrode can be improved and degradation of the metal-containing catalyst can be prevented by a halogen ion concentration of 150 to 6000 ppm, relative to the total mass of the fuel cell electrode. The halogen ion concentration does not reduce the performance of the fuel cell electrode when installed for its intended use.

[0012] The dependent claims relate to advantageous developments and embodiments of the invention.

[0013] In consideration of the balance between long-term stability and performance of a fuel cell electrode, the fuel cell electrode preferably has a halogen ion concentration of 300 to 3000 ppm relative to the total mass of the fuel cell electrode.

[0014] As already disclosed above, the halogen ions used are substantially not limited. Advantageously, the halogen ions are selected from the group consisting of fluoride ions, chloride ions, bromide ions, iodide ions and mixtures thereof, and chloride ions are preferred due to very high availability and processability and also due to their less harmful effects on health.

[0015] According to an advantageous improvement, the metal-containing catalyst comprises a noble metal or a mixture or alloy formed by two or more noble metals or a noble metal-non-noble metal alloy, the non-noble metal alloy being particularly suitable for use in a fuel cell electrode formed as a cathode, and the pure noble metal catalyst being particularly suitable for use in a fuel cell electrode formed as an anode.

[0016] It is preferred that the noble metal-non-noble metal alloy comprises a platinum alloy and / or the noble metal of the metal-containing catalyst comprises platinum and / or palladium.

[0017] Since degradation due to potential cycling of metal-containing catalysts is shown on the cathode side of fuel cells, the fuel cell electrode according to the present invention is preferably formed as a cathode.

[0018] In addition, according to the present invention, a diaphragm coated with a catalyst is also described, the diaphragm comprising a fuel cell electrode formed as above. By using the fuel cell electrode according to the present invention, the diaphragm coated with a catalyst according to the present invention (hereinafter referred to as CCM) is characterized by very high long-term stability while maintaining good performance. Therefore, the same advantageous effects as described above for the fuel cell electrode according to the present invention are obtained for the CCM according to the present invention. These advantageous effects are attributed to the halogen ion concentration of 150 to 6000ppm in the fuel cell electrode used.

[0019] In addition, according to the present invention, a method for preparing the fuel cell electrode disclosed above is also described. In a method step of the method of the present invention, the halogen ion concentration is increased in the fuel cell electrode so that the halogen ion concentration of the fuel cell electrode is 150 to 6000 ppm and preferably 300 to 3000 ppm relative to the total mass of the fuel cell electrode. Here, increasing the halogen ion concentration means that the halogen ions are added in the form of soluble salts and are not already introduced with other fuel cell electrode components (i.e., in particular ionomers and metal-containing catalysts). This or these halogen ions are added separately and thus independently of the remaining fuel cell electrode components.

[0020] By adding one or more halogen ions, fuel cells can be produced which have a higher long-term stability without causing a loss in performance. The method can be implemented without a high level of technical and time expenditure.

[0021] According to an advantageous refinement, the halogen ion concentration is increased by preparing the fuel cell electrode with a solution containing at least one halogen ion. By preparing with a halogen ion-containing solution, a very uniform distribution of the halogen ions in the fuel cell electrode can be achieved, so that the fuel cell electrode is equally well protected from degradation in each catalytically active area and thus does not cause performance losses during the intended use.

[0022] The fuel cell electrode can be prepared as a cathode or an anode. In particular, the anode or cathode is prepared from an anode dispersion or a cathode dispersion. A halogen ion-containing compound is added to the anode dispersion or the cathode dispersion, more precisely, such that the halogen ion weight proportion F in the anode dispersion is A Satisfy the following formula:

[0023] FA(A×B)

[0024] In the above formula, A is 150 to 6000 ppm and preferably 300 to 3000 ppm, and B is the solid ratio of the anode dispersion.

[0025] Alternatively, the halogen ion weight proportion F in the cathode dispersion is K Satisfy the following formula:

[0026] FK(A×B)

[0027] Wherein A is 150 to 6000 ppm and preferably 300 to 3000 ppm, and B is the solid proportion of the cathode dispersion.

[0028] As already disclosed above, the halogen ion is preferably selected from the group consisting of fluoride ion, chloride ion, bromide ion, iodide ion and mixtures thereof, and chloride ion is preferred due to very high availability and less harmful effects on health.

[0029] According to an advantageous refinement, the cation of the halogen ion-containing compound used to generate the desired halogen ion concentration is selected from the group consisting of protons, alkali metals, alkaline earth metals, ammonium or cationic organic compounds. Particularly preferred cations are Na + and K + .

[0030] In order to further simplify the method, a fuel cell electrode dispersion is prepared for producing the fuel cell electrode by dispersing a metal-containing catalyst and a proton-conducting ionomer and adding a halogen-containing compound to the fuel cell electrode dispersion before, during or after the dispersion. The addition of the halogen-containing compound is carried out in particular during further dispersion in order to achieve a uniform distribution of the halogen ions.

[0031] The method according to the invention can be used to produce a fuel cell electrode according to the invention. A fuel cell electrode produced according to the method described above is then also described, which is characterized by a high long-term stability without a simultaneous loss of performance.

[0032] In addition, according to the present invention, a catalyst-coated membrane is also described, the membrane comprising a cathode, an anode and a proton-conducting membrane located therebetween, wherein the cathode comprises a first metal-containing catalyst and a proton-conducting ionomer, wherein the cathode comprises a second metal-containing catalyst and a proton-conducting ionomer, and wherein the membrane comprises a proton-conducting ionomer.

[0033] According to the present invention, a diaphragm coated with a catalyst is understood to be a component in which an anode and a cathode surround both sides of a diaphragm so that the diaphragm is arranged between the cathode and the anode. The anode and the cathode can be directly coated on the diaphragm and form a composite. That is, in this case, it is particularly referred to as a CCM, i.e. a "catalyst coated diaphragm". In addition, a diaphragm coated with a catalyst is also understood to be a component for use in a fuel cell, in which the anode and the cathode are arranged on both sides of the diaphragm and are particularly laminated. In both cases, a gas diffusion layer (GDL) is provided on both sides of the exposed anode and the cathode. If a gas diffusion layer is provided, the entire assembly is also referred to as a membrane electrode assembly (MEA). According to the present invention, in the case of a diaphragm coated with a catalyst, the halogen ion concentration relates to the assembly without a GDL formed as above.

[0034] Relative to the total mass of the diaphragm coated with the catalyst, the diaphragm coated with the catalyst according to the present invention has a halogen ion concentration of 50 to 1000 ppm. The halogen ion concentration is therefore obtained as the sum of the individual halogen ion concentrations of the anode, cathode and diaphragm and is relative to the total mass of these components. The halogen ion concentration of 50 to 1000 ppm is not basically introduced by the metal-containing catalyst and the ionomer, but is explicitly added until the desired halogen ion concentration has been adjusted. As already described above for the fuel cell electrode, the halogen ion concentration in the diaphragm coated with the catalyst is determined by means of ion chromatography. By the selected sample preparation method or by selecting the halogen ions to be determined, only free halogen ions are detected, rather than halogen ions covalently bonded or otherwise (e.g., complexed) bonded in the diaphragm coated with the catalyst. By aqueous extraction and subsequent measurement by means of ion chromatography, fluoride ions present in the form of being bonded in the ionomer (e.g., in the case of using fluorinated ionomers) or in the diaphragm are clearly not detected at the same time.

[0035] The halogen ions are preferably present mainly in the cathode, since the cathode is particularly susceptible to catalyst degradation. However, since the halogen ions can partially move through the layers of the catalyst-coated membrane, the desired halogen ion concentration can also be set in the anode or even in the membrane. When the catalyst-coated membrane is used as intended, the effect in terms of the long-term stability of the catalyst-coated membrane is achieved by the halogen ions being evenly distributed in the layers and thus uniformly stabilizing without reducing the performance of the catalyst-coated membrane.

[0036] The halogen ion concentration of 50 to 1000 ppm, which is important for the present invention, with respect to the total mass of the catalyst-coated diaphragm is present not only in unused (i.e. newly manufactured) catalyst-coated diaphragms but also in catalyst-coated diaphragms during or after intended use. The reason for this is that the halogen ions can be added to the anode and / or cathode and / or diaphragm in the desired concentration, so that a halogen ion concentration of 50 to 1000 ppm is set in total relative to the total mass of the catalyst-coated diaphragm. Even when, for example, halogen ions are transferred from their initial component to other components of the catalyst-coated diaphragm (e.g. from cathode to anode or from anode to cathode or from cathode to diaphragm and / or anode or from anode to diaphragm and / or cathode) during intended use, the halogen ion concentration relative to the catalyst-coated diaphragm always remains unchanged, i.e. according to the present invention, it is 50 to 1000 ppm.

[0037] This is consistent with the fuel cell electrode of the invention described above. If such a fuel cell electrode according to the invention having a halogen ion concentration of 50 to 1000 ppm is used for a catalyst-coated membrane according to the invention, then as long as the halogen ion concentration in the fuel cell electrode used is at least 50 ppm but less than 1000 ppm, one or more halogen ions can also be added to other fuel cell electrodes and / or membranes, so that a total halogen ion concentration of 50 ppm to 1000 ppm is obtained in total relative to the total mass of the catalyst-coated membrane.

[0038] In the catalyst-coated membrane according to the present invention, a fuel cell electrode according to the present invention having a halogen ion concentration of less than 1000 ppm can also be combined with a fuel cell electrode not according to the present invention, for example, having a halogen ion concentration of less than 50 ppm relative to the total mass of the fuel cell electrode, as long as the halogen ion concentration of the catalyst-coated membrane is in the range of 50 to 1000 ppm relative to the total mass of the catalyst-coated membrane.

[0039] It is also possible to combine two fuel cell electrodes not according to the present invention, each having a halogen ion concentration of less than 50 ppm relative to the respective total mass of the corresponding fuel cell electrode, to form a catalyst-coated membrane according to the present invention, i.e., when a halogen ion concentration of 50 to 1000 ppm relative to the total mass of the catalyst-coated membrane is obtained.

[0040] However, the desired halogen ion concentration of preferably 50 to 1000 ppm relative to the total mass of the catalyst-coated membrane is introduced via the fuel cell, in particular via the cathode, so that the halogen ion concentration of the fuel cell (in the fuel cell relative to the total mass of the fuel cell) is reflected in the halogen ion concentration of the catalyst-coated membrane (relative to the total mass of the catalyst-coated membrane). However, when the catalyst-coated membrane is used as intended, the distribution of the halogen ions in the individual layers of the catalyst-coated membrane can be varied without changing the halogen ion concentration relative to the total mass of the catalyst-coated membrane according to the invention.

[0041] In order to achieve an improved balance between the effects of improving long-term stability while achieving high performance, the halogen ion concentration in the catalyst-coated membrane is preferably 50 to 500 ppm relative to the total mass of the catalyst-coated membrane.

[0042] As already disclosed above, the halogen ions used are substantially not limited. However, advantageously, the halogen ions are preferably selected from the group consisting of fluoride ions, chloride ions, bromide ions, iodide ions and mixtures thereof, and chloride ions are preferred due to very high availability and less harmful effects on health.

[0043] According to an advantageous improvement, the first metal-containing catalyst and the second metal-containing catalyst include a noble metal or a mixture or alloy formed of two or more noble metals or a noble metal-non-noble metal alloy.

[0044] It is preferred that the noble metal-non-noble metal alloy comprises a platinum alloy and / or the noble metal of the metal-containing catalyst comprises platinum and / or palladium.

[0045] According to another preferred improvement, the anode of the catalyst-coated diaphragm has a halogen ion weight proportion F corresponding to the following formula: A :

[0046]

[0047] Here, A is 50 to 1000 ppm and preferably 50 to 500 ppm, M CCM is the unit area weight of the catalyst-coated diaphragm and M CLA is the weight per unit area of ​​the anode.

[0048] In addition, the cathode of the catalyst-coated membrane preferably has a halogen ion weight ratio F corresponding to the following formula: K :

[0049]

[0050] Here, A is 50 to 1000 ppm and preferably 50 to 500 ppm, M CCM is the unit area weight of the catalyst-coated diaphragm and M CLK is the weight per unit area of ​​the cathode.

[0051] The above formula will be explained with the aid of the following examples, which are however intended to illustrate and not to limit the invention. For example, depending on the type, the membrane thickness is 8 to 20 μm, thereby obtaining 1.6 to 4 mg / cm 2 Weight per unit area (M CCM ).

[0052] For a separator with a separator thickness of 12 μm, 2.4 mg / cm 2 The unit area weight of the diaphragm is M CCM .

[0053] The weight per unit area of ​​the electrode (M CLA or M CLK ) depends on a number of factors:

[0054] - Catalyst loading (e.g. Pt and / or Pd)

[0055] - For example, the platinum content on the catalyst (usually 20% to 60% by weight)

[0056] - ionomer content (that is to say in particular the ratio of ionomer to carbon - I:C)

[0057] Example:

[0058] With 0.1mg(Pt) / cm 2 , 20 wt% Pt / C and an anode with an I:C of 0.8:1

[0059] →Weight per unit area (M CLA )=0.82mg / cm 2

[0060] With 0.5mg(PtCo) / cm 2 , 50% Pt / C and I:C 1:1 cathode

[0061] →Weight per unit area (M CLK )=1.5mg / cm 2

[0062] Total unit area weight (M CCM )=4.72mg / cm 2

[0063] Anode coefficient (F A )=5.76→F A =288-5760ppm

[0064] Cathode coefficient (F K )=3.15→F K =157-3150ppm

[0065] In addition, the present invention also provides a fuel cell having very good long-term stability while maintaining good performance. The fuel cell according to the present invention is characterized by comprising the above catalyst-coated membrane, whereby the above-explained advantageous effects are also obtained for the fuel cell.

[0066] The advantages, advantageous effects and refinements described in each case for the fuel cell electrode according to the invention, the separator coated with a catalyst according to the invention and the fuel cell according to the invention can each be applied interchangeably.

[0067] Furthermore, a method for preparing the catalyst-coated membrane disclosed above is also described according to the present invention. According to the method, a halogen ion concentration is added to the cathode and / or the anode and / or the proton-conducting membrane so that the halogen ion concentration of the catalyst-coated membrane is 50-1000 ppm, preferably 50-500 ppm, relative to the total mass of the catalyst-coated membrane. The halogen ion concentration is thus a combination of the individual halogen ion concentrations of the anode, cathode and membrane and is relative to the total mass of these elements / components.

[0068] The desired halogen ion concentration is obtained by adding one or more halogen ions, that is, the desired halogen ion concentration is not obtained by using a halogen ion-containing catalyst precursor and a halogen ion-containing ionomer, but the corresponding elements are explicitly added to the catalyst-coated membrane to be prepared.

[0069] Due to the halogen ion concentration of 50 to 1000 ppm and preferably 50 to 500 ppm, the long-term stability of the catalyst-coated membrane is improved without loss of performance. The method can be easily implemented without high technical effort and is therefore very efficient.

[0070] The method for producing a catalyst-coated membrane according to the present invention is suitable for producing a catalyst-coated membrane according to the present invention.

[0071] In order to achieve a particularly uniform halogen ion concentration in the catalyst-coated membrane, the catalyst-coated membrane is prepared with at least one solution containing halogen ions. As long as the desired halogen ion concentration relative to the total weight of the catalyst-coated membrane is achieved, the preparation with the aid of a solution containing halogen ions can be carried out in one or more or even all layers of the catalyst-coated membrane. The preparation of the catalyst-coated membrane using a halogen ion solution can be technically particularly simple to achieve and does not require a high technical effort and can achieve a particularly uniform distribution of the halogen ions in the corresponding layer.

[0072] According to an advantageous development, the anode is produced from an anode dispersion and the cathode is produced from a cathode dispersion, wherein a compound containing halogen ions is added to the anode dispersion and / or the cathode dispersion, wherein the weight proportion of the halogen ions in the anode dispersion is F A Satisfy the following formula:

[0073]

[0074] Here, A is 50 to 1000 ppm and preferably 50 to 500 ppm, B is the solid ratio of the anode dispersion, MCCM is the unit area weight of the catalyst-coated diaphragm and M CLA is the weight per unit area of ​​the anode.

[0075] Alternatively or additionally, the halogen ion weight proportion F in the cathode dispersion is K Satisfy the following formula:

[0076]

[0077] Here, A is 50 to 1000 ppm and preferably 50 to 500 ppm, B is the solid content of the cathode dispersion, M CCM is the unit area weight of the catalyst-coated diaphragm and M CLK is the weight per unit area of ​​the cathode.

[0078] The anode dispersion and the cathode dispersion can have different halogen ion weight proportions.

[0079] The halogen ion is also essentially unrestricted and can be selected from the group consisting of fluoride ion, chloride ion, bromide ion or iodide ion, with chloride ion being particularly preferred as halogen ion.

[0080] Due to good solubility, the cation of the halogen ion-containing compound used to adjust the halogen ion concentration is selected from the following group: protons, alkali metals, alkaline earth metals, ammonium or cationic organic compounds. Particularly preferred cations are Na + and K + .

[0081] In order to further simplify the method, the anode dispersion and cathode dispersion are applied directly to the separator or via a decal substrate.

[0082] According to another advantageous refinement, a cathode dispersion is prepared to produce the cathode by dispersing a first metal-containing catalyst and a proton-conducting ionomer. Additionally, an anode dispersion is prepared to produce the anode by dispersing a second metal-containing catalyst and a proton-conducting ionomer. Furthermore, a halogen-containing compound is added to the cathode dispersion and / or the anode dispersion before, during or after the dispersion, so that the desired halogen ion concentration can be set.

[0083] Dispersion can be carried out using conventional technical aids and can be achieved technically simply and quickly due to the very good solubility of the halogen ion-containing compounds in most cases.

[0084] Exemplary method steps for producing a catalyst-coated membrane according to the invention are given below. Further method steps may be provided.

[0085] Preparation of catalyst dispersion

[0086] The catalyst dispersion (also referred to as fuel cell electrode dispersion) is prepared by mixing water, a metal-containing catalyst in a solvent and an ionomer dispersion. The ionomer used in the catalyst layer according to the present invention is not specifically limited and can be a perfluorinated ionomer (PFSA), a partially fluorinated or hydrocarbon-based (unfluorinated) ionomer. The catalyst dispersion is ground in a ball mill (grinding media: ZrO2 balls) for about 120 minutes. The catalyst layer is prepared by applying the catalyst dispersion to an inert substrate (so-called decal) and drying.

[0087] Alternatively, for example, ultrasound or various grinding mills can also be used in the preparation of the dispersion. Grinding mills include, for example, ball mills, stirred bead mills, agitator mills, attritors and special roller mills.

[0088] To prepare a catalyst dispersion according to the invention having a lower chloride ion concentration, the required amount of a 5 mass percent aqueous sodium chloride solution was added to the catalyst ink after the above-described dispersion process, followed by stirring on a magnetic stirrer for at least two hours. To set a higher chloride ion concentration, the required amount of a 20 mass percent aqueous sodium chloride solution was added to the catalyst ink after the dispersion process, followed by stirring on a magnetic stirrer for at least two hours.

[0089] Preparation of the catalyst-coated diaphragm of the present invention

[0090] The cathode layer and the anode layer formed by the correspondingly prepared anode dispersion and cathode dispersion can be coated on an inert film and dried. As coating, conventional techniques such as slot dies, scrapers, spiral applicators, screen printing or spraying devices can be considered. These layers are then transferred to the diaphragm in a laminating process (so-called decal method), wherein the laminating temperature is generally 150 to 190 ° C and a pressure of 1 to 3 MPa is applied. For example, lamination can be carried out continuously in a press or between roller pairs. The lamination duration in the press during discontinuous operation is about one minute, while for a continuous method, the lamination duration can also be only a few seconds.

[0091] In an alternative method, the cathode and / or anode can also be applied directly to the separator and dried (direct printing method).

[0092] As a further alternative, the cathode and / or anode can also be applied to a gas diffusion layer (GDL) and dried to obtain a so-called gas diffusion electrode (GDE), which is then brought into contact with a membrane to obtain a membrane electrode assembly (GDE process).

[0093] As a further alternative, the first electrode may be applied to the membrane (by decaling or by direct printing) and the second electrode applied to the GDL.

[0094] Different methods of producing the membrane electrode assembly may be regarded as equivalent in the sense of the present invention.

[0095] The method for preparing a catalyst-coated diaphragm according to the present invention can be used to prepare a catalyst-coated diaphragm according to the present invention. Then, a catalyst-coated diaphragm prepared according to the above method is also described, and the catalyst-coated diaphragm is characterized by high long-term stability without performance loss. Example

[0096] The present invention is explained in detail below with reference to examples and drawings.

[0097] In the attached picture:

[0098] Figure 1 A schematic diagram showing a catalyst-coated diaphragm according to one embodiment is shown in cross section,

[0099] Figure 2 shows the voltage loss after 30000 potential cycles between 0.6 and 0.95 V,

[0100] Figure 3 shows the mass activity loss after 30000 potential cycles between 0.6 and 0.95 V,

[0101] Figure 4 shows the EPSA (catalyst surface area) loss after 30,000 potential cycles between 0.6 and 0.95 V,

[0102] Figure 5 The long term chemical stability of a sample without chloride (solid line) and a sample with a measured value of 220 ppm chloride (dashed line) is shown, and

[0103] Figure 6 It is shown that at the beginning of the measurement, the 2 The battery voltage of each example is shown below.

[0104] Only the key elements and components of the present invention are shown in the figure. For the sake of brevity, all other elements and components are omitted.

[0105] Figure 1A schematic diagram of a catalyst-coated membrane 1 according to one embodiment is shown in a cross-sectional view. The catalyst-coated membrane 1 comprises a cathode 2, an anode 3 and a proton-conducting membrane 4 located therebetween, wherein the cathode 2 comprises a first metal-containing catalyst 5 and a proton-conducting ionomer 6, the cathode 3 comprises a second metal-containing catalyst 7 and a proton-conducting ionomer 8, and the membrane 4 comprises a proton-conducting ionomer. The catalyst-coated membrane 1 has a halogen ion concentration of 50 to 1000 ppm relative to the total mass of the catalyst-coated membrane 1. The halogen ions 9 are in particular chloride ions and are hereby explicitly arranged in the cathode 2. Particularly preferably, the halogen ions 9 have been introduced into the cathode 3 in the form of a NaCl solution.

[0106] Due to the concentration of halide ions, the catalyst-coated membrane 1 is characterized by very good long-term stability without significant performance losses.

[0107] Potential Cycling Test

[0108] The potential cycling test is an accelerated stability test which simulates the voltage curve of the cathode during dynamic operating operation of the fuel cell, ie under normal operating conditions, wherein the performance of the fuel cell is captured.

[0109] The potential cycling test complies with the recommendations of the U.S. Department of Energy (DOE) and is performed as follows:

[0110] Temperature of a single battery T 电池 The temperature of the humidifier was 80°C for the anode and 80°C for the cathode. Hydrogen was introduced to the anode and nitrogen to the cathode at ambient pressure. A square wave voltage was applied to the cell, in which a voltage of 0.6 V for 3 seconds and a voltage of 0.95 V for 3 seconds were applied alternately. This cycle was repeated 30,000 times.

[0111] Long-term chemical stability testing

[0112] The long-term chemical stability test is an accelerated stability test which tests the hydrogen permeation of a catalyst-coated membrane during operation at an open circuit clamping voltage.

[0113] Long-term chemical stability testing complies with the U.S. Department of Energy (DOE) recommendations and is performed as follows:

[0114] Battery temperature T 电池 The temperature was 90°C and the humidification was set to 30% relative humidity. Hydrogen was directed to the anode and air to the cathode at 1.5 bar. No current was drawn so that the cell existed at the open circuit clamping voltage. The hydrogen permeation was measured at regular intervals.

[0115] Ion chromatography for determination of halogen ion content

[0116] Before the determination of the halogen ion content (especially chloride ion) by means of ion chromatography, the sample is prepared by oxygen pressure digestion. Here, the sample material is burned under pressure and with the addition of oxygen in a closed system.

[0117] Halogen ions in fuel cell electrodes are determined by means of ion chromatography. Halogen ions can be distinguished by retention time via ion chromatography (retention time: for example, F: 6.9 minutes, Cl: 10.4 minutes, Br: 15.9 minutes). Here, a mixture of 1.9 L of an aqueous solution of sodium carbonate with a concentration of 3.2 mmol / L and sodium bicarbonate with a concentration of 1.0 mmol / L and 0.1 L of acetonitrile is used, resulting in a total of 2.0 L of eluent. The measurement is performed using an instrument Metrohm 690IC (Germany, Deutsche METROHM GmbH & Co. KG). Metrosep A Supp7-250 / 4.0 mm (Germany, Deutsche METROHM GmbH & Co. KG) is used as a column. The column temperature is set to 40 ° C and the flow rate is 0.7 mL / min.

[0118] Example 1

[0119] The catalyst-coated diaphragm was prepared as described above. The cathode prepared according to Example 1 included a pure platinum catalyst supported on carbon (50% by mass of platinum, 50% by mass of carbon) as the catalyst. The weight per unit area of ​​the noble metal containing metal catalyst was 0.4 mg. pt / cm 2 The cathode also includes an ionomer having an equivalent weight (EW) of 790 g / mol ( D79-25BS; Solvay Specialty Polymers, Italy). The mass ratio of ionomer to carbon-containing support material is 0.8:1.

[0120] The cathode according to the invention according to Example 1 also comprises sodium chloride in a concentration of 1370 to 1500 ppm chloride ions, determined by means of ion chromatography as described above.

[0121] The anode prepared according to Example 1 includes a pure platinum catalyst supported on carbon (20 mass % platinum, 80 mass % carbon) as a catalyst. The weight per unit area of ​​the noble metal containing metal catalyst is 0.1 mg pt / cm 2 The anode also includes an ionomer having an equivalent weight (EW) of 790 g / mol ( D79-25BS; Italy, Solvay SpecialtyPolymers). The mass ratio of ionomer to carbon-containing support material is 0.8:1.

[0122] The MEA prepared according to Example 1 was prepared according to the decal method described previously. The anode and cathode were applied to a glass fiber reinforced PTFE substrate using a spiral applicator. The wet layer thickness was selected to achieve the target load. The corresponding catalyst dispersion was then dried in a furnace at 100° C. for 5 minutes. The anode and cathode and the diaphragm (perfluorinated enhanced sulfonic acid diaphragm, 15 μm thick) were laminated (decal transfer) for 1 minute at a temperature of 180° C. and a pressure of 1 MPa in a belt press.

[0123] The chloride ion content of the catalyst-coated membrane was therefore 310 to 340 ppm chloride ions.

[0124] Examples 2 and 3, Comparative Examples 1 to 3

[0125] Examples 2 and 3 and Comparative Examples 1 to 3 were prepared similarly to Example 1, except that the compositions shown in Table 1 below were used.

[0126] Table 1 below gives an overview of the experiments performed and the corresponding test results. Examples and comparative examples, their corresponding chloride ion content and the losses caused by the potential cycling test between 0.6 and 0.95 V are shown. (Value at the beginning of the test minus value at the end of the test)

[0127] Table 1

[0128]

[0129] As non-graphitized carbon, for example, carbon under the trademark Vulcan from Cabot Corporation can be used. "EPSA" here means effective platinum surface area, i.e. the effective platinum surface area. The term "geo" relates to the geometric active area of ​​the membrane coated with the catalyst. EPSA thus means the platinum surface area [cm2] per unit area of ​​the membrane coated with the catalyst. 2 (Pt)].

[0130] like Figures 1 to 3 As shown, due to the chloride ion concentration being set in the range of 50 to 1000 ppm, the examples of the present invention show much smaller voltage loss after 30,000 potential cycles between 0.6 and 0.95 V compared to the comparative examples without added halogen ions (see Figure 2 ), smaller mass activity loss after 30,000 potential cycles between 0.6 and 0.95 V (see Figure 3) and a smaller EPSA loss after 30,000 potential cycles between 0.6 and 0.95 V (effective Pt surface area - Pt surface area relative to electrode surface area; that is, EPSA represents the Pt surface area per unit area of ​​the diaphragm coated with catalyst [cm 2 (Pt)])(see Figure 4 ).

[0131] Chloride ions in the ppm range used resulted in reduced voltage losses, mass activity losses and also EPSA losses. In addition, no negative effects on the long-term chemical stability were observed, especially from Figure 5 No effect of increasing H2O2 concentration was observed.

[0132] Figure 6 It is shown that the chloride ion content has no significant effect on the battery voltage, that is, it does not cause degradation of the battery voltage.

[0133] In addition to the above textual description of the present invention, in order to supplement the disclosure thereof, explicit reference is hereby made to Figures 1 to 6 A graphical representation of the present invention.

[0134] List of Reference Numerals

[0135] 1 Catalyst-coated diaphragm

[0136] 2 cathode

[0137] 3 Anode

[0138] 4 Diaphragms

[0139] 5. The first metal-containing catalyst

[0140] 6 Proton Conducting Ionomers

[0141] 7. Second metal-containing catalyst

[0142] 8 Proton Conducting Ionomer

[0143] 9 Halogen ions

Claims

1. A fuel cell electrode (2, 3) comprising a metal-containing catalyst (5, 7) and a proton-conducting ionomer (6, 8), wherein: The fuel cell electrode (2, 3) has a halogen ion concentration of 150 to 6000 ppm relative to the total mass of the fuel cell electrode (2, 3).

2. The fuel cell electrode (2, 3) according to claim 1, wherein: The fuel cell electrode (2, 3) has a halogen ion concentration of 300 to 3000 ppm relative to the total mass of the fuel cell electrode (2, 3), and / or The halogen ion is selected from the group consisting of fluoride ion, chloride ion, bromide ion, iodide ion and mixtures thereof and is preferably chloride ion.

3. A fuel cell electrode (2, 3) according to any one of the preceding claims, wherein the metal-containing catalyst (5, 7) comprises a noble metal or a mixture or alloy formed by two or more noble metals or a noble metal-non-noble metal alloy, wherein in particular the noble metal-non-noble metal alloy comprises a platinum alloy and / or wherein in particular the noble metal of the metal-containing catalyst (5, 7) comprises platinum and / or palladium.

4. A fuel cell electrode (2, 3) according to any one of the preceding claims, formed as a cathode (2).

5. Catalyst-coated membrane (1) comprising a fuel cell electrode (2, 3) according to any one of the preceding claims.

6. A method for preparing a fuel cell electrode (2, 3) according to any one of claims 1 to 4, wherein the halogen ion concentration is added to the fuel cell electrode (2, 3) so that the halogen ion concentration of the fuel cell electrode (2, 3) is 150 to 6000 ppm, preferably 300 to 3000 ppm, relative to the total mass of the fuel cell electrode (2, 3).

7. The method according to claim 6, wherein the fuel cell electrode (2, 3) is prepared using a solution comprising at least one halogen ion.

8. The method according to claim 6 or 7, wherein the fuel cell electrode (2, 3) is prepared as an anode (3) formed from an anode dispersion or a cathode (2) formed from a cathode dispersion, wherein a halogen ion-containing compound is added to the anode dispersion or the cathode dispersion, wherein the halogen ion weight proportion F in the anode dispersion is A Satisfy the following formula: F A =(A×B) wherein A is from 150 to 6000 ppm and preferably from 300 to 3000 ppm, and B is the solid proportion of the anode dispersion, or The weight proportion of the halogen ions in the cathode dispersion is K Satisfy the following formula: F K =(A×B) wherein A is from 150 to 6000 ppm and preferably from 300 to 3000 ppm, and B is the solid proportion of the cathode dispersion, wherein the anode dispersion and the cathode dispersion may have different halide ion weight proportions, and / or The cation of the compound containing halogen ions is selected from the group consisting of protons, alkali metals, alkaline earth metals, ammonium or cationic organic compounds, and / or A fuel cell electrode dispersion is prepared for producing the fuel cell electrode (2, 3) by dispersing a metal-containing catalyst (5, 7) and a proton-conducting ionomer (6, 8) and adding a halogen ion-containing compound to the fuel cell electrode dispersion before, during or after the dispersion.

9. A catalyst-coated membrane comprising a cathode (2), an anode (3) and a proton-conducting membrane (4) located therebetween, wherein a. The cathode (2) comprises a first metal-containing catalyst (5) and a proton-conducting ionomer (6), b. the cathode (3) comprises a second metal-containing catalyst (7) and a proton-conducting ionomer (8), and c. The diaphragm (4) comprises a proton conducting ionomer, wherein: The catalyst-coated membrane (1) has a halogen ion concentration of 50 to 1000 ppm relative to the total mass of the catalyst-coated membrane (1).

10. The catalyst-coated diaphragm (1) according to claim 9, wherein: The catalyst-coated diaphragm (1) has a halogen ion concentration of 50 to 500 ppm relative to the total mass of the catalyst-coated diaphragm (1), and / or wherein the halogen ion is selected from the group consisting of fluoride ion, chloride ion, bromide ion, iodide ion and mixtures thereof and is preferably chloride ion, and / or The first metal-containing catalyst (5) and the second metal-containing catalyst (7) comprise a noble metal or a mixture or alloy formed by two or more noble metals or a noble metal-non-noble metal alloy, wherein in particular the noble metal-non-noble metal alloy comprises a platinum alloy and / or in particular the noble metal of the second metal-containing catalyst (7) comprises platinum and / or palladium.

11. The catalyst-coated membrane (1) according to claim 9 or 10, wherein the anode (3) has a halogen ion weight proportion F corresponding to the following formula A : wherein A is 50 to 1000 ppm and preferably 50 to 500 ppm, and M CCM is the weight per unit area of ​​the catalyst-coated diaphragm (1) and M CLA is the weight per unit area of ​​the anode (3), or The cathode (2) has a halogen ion weight ratio F corresponding to the following formula K : wherein A is 50 to 1000 ppm and preferably 50 to 500 ppm, and M CCM is the weight per unit area of ​​the catalyst-coated diaphragm (1) and M CLK is the weight per unit area of ​​the cathode (2).

12. A fuel cell comprising the catalyst-coated membrane according to any one of claims 9 to 11.

13. A method for preparing a catalyst-coated membrane (1) according to any one of claims 9 to 11, wherein the halogen ion concentration is added to the cathode (2) and / or the anode (3) and / or the proton conductive membrane (4) so ​​that the halogen ion concentration of the catalyst-coated membrane (1) is 50-1000 ppm, preferably 50-500 ppm, relative to the total mass of the catalyst-coated membrane (1).

14. The method according to claim 13, wherein the catalyst-coated membrane (1) is prepared with a solution comprising at least one halide ion, and / or wherein the anode (3) is prepared from an anode dispersion and the cathode (2) is prepared from a cathode dispersion, wherein a compound containing halogen ions is added to the anode dispersion and / or the cathode dispersion, The weight proportion of the halogen ions in the anode dispersion is A Satisfy the following formula: wherein A is 50 to 1000 ppm and preferably 50 to 500 ppm, B is the solid ratio of the anode dispersion, and M CCM is the weight per unit area of ​​the catalyst-coated diaphragm (1) and M CLA is the weight per unit area of ​​the anode (3), and / or The weight proportion of the halogen ions in the cathode dispersion is K Satisfy the following formula: wherein A is 50 to 1000 ppm and preferably 50 to 500 ppm, B is the solid ratio of the cathode dispersion, and M CCM is the weight per unit area of ​​the catalyst-coated diaphragm (1) and M CLK is the weight per unit area of ​​the cathode (2), wherein the anode dispersion and the cathode dispersion may have different halide ion weight proportions, and / or The cation of the compound containing halogen ions is selected from the group consisting of protons, alkali metals, alkaline earth metals, ammonium or cationic organic compounds, and / or wherein the anode dispersion and the cathode dispersion are applied directly to the separator (4) or via a decal substrate, and / or A cathode dispersion is prepared for preparing the cathode (2) by dispersing a first metal-containing catalyst (5) and a proton-conducting ionomer (8), and an anode dispersion is prepared for preparing the anode (3) by dispersing a second metal-containing catalyst (7) and a proton-conducting ionomer (8) and adding a halogen ion-containing compound to the cathode dispersion and / or the anode dispersion before, during or after the dispersion.